1993
DOI: 10.1902/jop.1993.64.6.538
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Indices Around Natural and Titanium Abutments: A Longitudinal Multicenter Study

Abstract: This multicenter prospective study on the use of an implant system involved 9 centers and reports on the periodontal aspects after 3 years of observation. A total of 558 implants in 159 patients with 197 bridges all independent from natural teeth were originally included. Because of failures and patient withdrawals the number of implants was reduced to 460 and bridges to 174. The cumulative success rate for implants, starting from implant placement, is 94.3% after 2 years and 93.9% after 3 years indicating a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
46
3
10

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 7 publications
6
46
3
10
Order By: Relevance
“…This may be due to adequate oral hygiene maintenance by the patient during post-operative evaluation period. These findings are not in accordance with multicenter longitudinal study by Van Steenberghe et al who concluded that there is a decrease of probing depth over time, 23 and George et al 24 who reported significant greater probing depths with increasing time. The Consensus report of the 1996 workshop in periodontics concluded that there is no clear evidence of value of probing depth.…”
Section: S351contrasting
confidence: 62%
“…This may be due to adequate oral hygiene maintenance by the patient during post-operative evaluation period. These findings are not in accordance with multicenter longitudinal study by Van Steenberghe et al who concluded that there is a decrease of probing depth over time, 23 and George et al 24 who reported significant greater probing depths with increasing time. The Consensus report of the 1996 workshop in periodontics concluded that there is no clear evidence of value of probing depth.…”
Section: S351contrasting
confidence: 62%
“…Therefore, the high detection rates indicate that the risk of failure is higher in patients colonized by P. gingivalis and P. intermedia, and the importance of thorough maintenance such as professional dental plaque control has been suggested. The relationship between dental plaque control conditions in the implant region and marginal bone loss has been reported 20,[30][31][32] , suggesting the importance of plaque control in the implant region. In recent years, implant treatment has been performed in patients with periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, transcription of tissues, even after long clinical function (Buser et al, 1992; cytokines essential to increase the osteoclast precursor pool, Steenberghe et al, 1993;Mericske-Stem et al, 1994). The lack such as SCF, or able to induce osteoclast differentiation, such of IL-1 and TNF-a.…”
Section: Discussionmentioning
confidence: 99%